Evolutionary Optimisation of Semi-Transparent Building Integrated Photovoltaic Facades. (March 2014) - Choo, Thian-Siong; Janssen, Patrick
The optimisation of semi-transparent building integrated photovoltaic facades can be challenging when attempting to find an overall balance performance between conflicting performance criteria. This paper presents a three-phase design optimisation method that maximises overall electricity savings generated by these types of facades by simulating the combined impact of electricity generation, cooling load, and daylight autonomy. Two demonstrations are performed, with the difference being that the second demonstration uses an enhanced model for calculating daylight savings that takes into account the use of blinds to counteract glare. For both demonstrations, the three-phase optimisation method significantly reduces optimisation run times. Comparing the design variants evolved by the two demonstrations, the use of the enhanced daylight savings model results in a total electricity savings that is more accurate but in terms of visual differentiation, the difference between the optimized design variants is relatively small.